Gambaran Perundungan dan Depresi pada Mahasiswa Universitas X - Namira Inaya Mokodongan; Lydia Edmay Viveca David; Jehosua Samratson Victor Sinolungan (Jurnal Impresi Indonesia, 2026)
Background: Bullying and depression are psychological problems that continue to occur in university environments and have significant impacts on students’ mental well-being. Purpose : To describe the forms of bullying and the levels of depression among students of the Faculty of Social and Political Sciences at Sam Ratulangi University. Methods: This study used a descriptive quantitative design with the Olweus Bully Victim Questionnaire (OBVQ) and the Beck Depression Inventory-II (BDI-II) as research instruments. A total of 162 third-semester students participated and the data were analyzed using descriptive statistics. Results: The majority of students experienced bullying in the low category, particularly in verbal and relational forms, while physical bullying was rarely reported. Depression levels showed that half of the respondents were in the normal category, while the remainder experienced mild to severe depression. Conclusion: Although the bullying experienced by students generally occurred at low intensity, it was still associated with the emergence of depressive symptoms. This highlights the need for institutional attention toward bullying prevention and the provision of adequate mental health support for students.